Double Pseudoaneurysm of the Superficial Palmar Arch: A Unique Case - Munoli, Amarnath; Tiwari, Pranita; Ashwini, Topugonda; Gajbhare, Abhijeet (Indian Journal of Plastic Surgery, 2023)
We present the case of a 22-year-old male patient who developed “double” pseudoaneurysm of the superficial palmar arch of the left hand after trivial trauma with a kitchen knife. Following an unsuccessful embolization attempt, surgical excision of the pseudoaneurysm was performed during which the pseudoaneurysm was found to arise from the anterior wall of the palmar arch. Intraoperatively, a second pseudoaneurysm arising from the deeper surface of the superficial palmar arch was found and excised. This is probably the only reported case of double pseudoaneurysm of the palmar arch in literature. The possible mechanism of arterial injury, diagnosis, and management is discussed.
Keywords: pseudoaneurysm; false aneurysm; double pseudoaneurysm; palmar arch